Jamaica : Financial Sector Assessment - World Bank (Washington, DC, 2015)
Jamaica has experienced 30 years of low economic growth and high fiscal deficits, with a significant impact on the development of the financial sector. As part of the overall growth and competitiveness reform agenda, the authorities have embarked on ambitious financial sector legislation reforms to address weaknesses. Lack of access to credit and equity constrain Micro, Small and Medium Sized Enterprise (MSME) operations and growth, and ultimately their contribution to the economy. High interest rates and low penetration of credit to households and MSMEs can be explained by high credit risk as a result of high information asymmetries in the market, as well as limited competition in the banking sector. The authorities should complete the establishment of a regulatory and supervisory framework for deposit-taking institutions proportionate to the risks and the activities they undertake. The impact of public policies has been limited and programs on housing, MSME finance, and agriculture finance would be welcomed to address market gaps, in support of financial inclusion. The financial inclusion agenda also requires a comprehensive strategy on consumer protection regulation and supervision.